Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19 - Nurjanah Zakiyah; Nurhikma Nurhikma; Asiyah Asiyah (UIN Sultan Maulana Hasanudin Banten, 2021)
This study aims to determine the parenting applied by parents in shaping the disciplined character of children aged 5-6 years during the covid-19 pandemic on Jalan Kebun Indah RT 05 RW 01 Kel. Sukarami district. As wide as Bengkulu City. This type of research is field qualitative and descriptive. This study uses data collection techniques through interviews, observation, and documentation. The data obtained through this method is used to facilitate data analysis, then interpreted by means of inductive thinking, namely based on special knowledge then a general solution is taken, so as to produce conclusions that can be accounted for. The results showed that the parenting applied by parents in shaping the disciplined character of children aged 5-6 years during the covid-19 pandemic on Jalan Kebun Indah RT 05 RW 01 Kel. Sukarami district. The width of Bengkulu City has been used well. This is evidenced by the child's disciplinary behavior. Although there are differences in discipline in each child.